2022
DOI: 10.1111/jgs.17810
|View full text |Cite
|
Sign up to set email alerts
|

Increased multimorbidity is associated with impaired cerebral and peripheral hemodynamic stabilization during active standing

Abstract: Background Age‐related morbidities and frailty are associated with impaired blood pressure (BP) and heart rate (HR) recovery after standing. Here we investigate how multimorbidity affects cerebral and peripheral hemodynamics during standing in a large sample of older patients. Methods Patients were recruited from a national Falls and Syncope Unit. They underwent an active stand test (5–10 min lying +3 min standing) with monitoring of continuous BP, HR, total peripheral resistance (TPR), stroke volume (SV), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Figure 1 describes the signal features extracted for univariate analysis. These features were also described in ( 41 ). Briefly, for SBP, DBP, and TSI, the nadir was detected as the minimum value between 5 and 40 seconds post-stand and the overshoot as the first peak after the nadir and before 60 seconds after stand.…”
Section: Discussionmentioning
confidence: 98%
“…Figure 1 describes the signal features extracted for univariate analysis. These features were also described in ( 41 ). Briefly, for SBP, DBP, and TSI, the nadir was detected as the minimum value between 5 and 40 seconds post-stand and the overshoot as the first peak after the nadir and before 60 seconds after stand.…”
Section: Discussionmentioning
confidence: 98%
“…Frailty reflects reduced physiological reserve and increased vulnerability to stressors and is considered a marker of biological aging ( 4 , 47 ). People with frailty have been shown to have impaired stabilization of cerebral oxygenation during postural change, which can be independent of the arterial blood pressure response ( 7 , 8 ). In addition, previous research suggested that frailty may lower the threshold of brain pathologies needed to trigger the clinical presentation of dementia ( 23 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that people with frailty were more likely to have orthostatic intolerance, which is generally considered a result of insufficient cerebral perfusion ( 3 , 6 ). In addition, recent data showed that slow walking speed, an indicator of frailty, and multimorbidity, a risk factor for frailty, were both associated with impaired stabilization of cerebral oxygenation independently of arterial blood pressure response ( 7 , 8 ). It is possible that frailty adds to the effects of OH on end-organ perfusion and modifies the effects of OH on morbidity and mortality.…”
mentioning
confidence: 99%
“…The measure used to evaluate the recovery of BP, following the initial drop that occurs after standing, was the recovery response rate, or the speed of BP increase. This measure was previously used to assess early hemodynamic responses after standing [38] and it can be useful for assessing the effectiveness of the autonomic system in recovering from the BP drop.…”
Section: Discussionmentioning
confidence: 99%
“…The time of standing was considered as the moment at which the participant initiated the change of position, identified with the height correction unit of the Finometer. The recovery of SBP and DBP was described as the slope measured between the point where BP reaches the nadir and where it peaks after that (the overshoot, in most cases) [38] ( Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%